A modified ternary composite lithium manganese iron phosphate material and its preparation method and application

Through the doping and coating technology of modified ternary composite lithium manganese iron phosphate material, the problem of taking into account both energy density and safety performance of the lithium-ion battery positive electrode material is solved, significantly improving the material's circulation performance and thermal stability, realizing the High energy density and safety performance.

CN115911334BActive Publication Date: 2024-12-13EVE POWER CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211651669.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-21
Publication Date
2024-12-13
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

Existing lithium-ion battery positive electrode materials are difficult to take into account high energy density and safety performance, especially ternary materials have shortcomings in structural and thermal stability, resulting in poor safety performance and high cost.

Method used

The modified ternary composite lithium manganese iron phosphate material is used to optimize the long cycle performance of the positive electrode material through doping and coating technology, and the phase change is suppressed by synergistic effects of the cationic cladding layer and metal oxide layer in the double-layer cladding layer. Enhance structural stability and reduce side reactions.

Benefits of technology

A positive electrode material that takes into account both energy density and safety performance has been achieved, which significantly improves the circulation performance and thermal stability of the material. The gram capacity reaches ≥158mAh/g, the soft pack energy density is ≥200Wh/kg, and the 200-week retention rate of 1C cycle is ≥97.1%. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115911334B_ABST
    Figure CN115911334B_ABST
Patent Text Reader

Abstract

The present invention relates to a modified ternary composite lithium iron manganese phosphate material and a preparation method and application thereof. The modified ternary composite lithium iron manganese phosphate material includes a composite modified ternary material and a modified lithium iron manganese phosphate material; the modified ternary material includes a ternary material, a double-layer coating layer of the ternary material and a ternary material doped metal ion; the double-layer coating layer of the ternary material includes a ternary material metal oxide layer and a ternary material cation coating layer; the modified lithium iron manganese phosphate material includes a lithium iron manganese phosphate material, a double-layer coating layer of lithium iron manganese phosphate and a lithium iron manganese phosphate doped metal ion; the double-layer coating layer of the lithium iron manganese phosphate includes a lithium iron manganese phosphate metal oxide layer and a lithium iron manganese phosphate cation coating layer. The ternary material and the lithium iron manganese phosphate are composited to obtain a positive electrode material that takes into account both energy density and safety. The ternary material and the lithium iron manganese phosphate are both doped and coated for modification, and the synergistic effect of doping and coating can be used to optimize the long cycle performance of the positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of manufacturing cathode materials for lithium-ion batteries, and relates to a modified ternary composite lithium iron manganese phosphate material, a preparation method thereof, and an application thereof. Background Art

[0002] With the development of society and the increasingly severe environmental pollution problems, the development of new energy has attracted more and more attention. In recent years, lithium-ion batteries have become one of the research hotspots of scientific researchers. Lithium-ion batteries have the advantages of high voltage, high energy density, long cycle life, no memory effect, and environmental friendliness.

[0003] Lithium iron manganese phosphate is a new type of phosphate cathode material for lithium-ion batteries formed by doping a certain proportion of manganese on the basis of lithium iron phosphate. Lithium iron manganese phosphate maintains the stable olivine-type structure of lithium iron phosphate, and the structure is more stable during charge and discharge. Even if all lithium ions are extracted during charging, the structure will not collapse, so the safety is better and the cost is lower. The application of pure lithium iron manganese phosphate has the advantages of lower cost and higher safety performance compared with ternary materials. The main limitations are low conductivity and low energy density. The advantage of ternary batteries in the application of new energy fields is high energy density, but their safety performance is poor, and it is difficult to pass safety tests such as acupuncture and impact, and a relatively perfect battery management system is required for control; in addition, with the increase in the prices of nickel and cobalt, the cost of ternary batteries is also relatively high.

[0004] CN 104300123A discloses a mixed cathode material, a cathode sheet using the cathode material, and a lithium-ion battery. The mixed cathode material includes the following components in parts by weight: 50-90 parts of nickel cobalt manganese ternary material, 10-50 parts of lithium iron manganese phosphate, and its energy density reaches 170 Wh / kg.

[0005] CN 105449269A provides a lithium-ion battery, including a cathode sheet, an anode sheet, a separator, and an electrolyte. The surface of the cathode sheet is coated with a cathode slurry. The cathode slurry includes a cathode active material. The cathode active material includes lithium iron phosphate, a ternary material, and lithium iron manganese phosphate; the general formula of the ternary material is LiNi x Co y Mn 1-x-y O2, where 0 < x < 1, 0 < y < 1, and 0 < x + y < 1. The mass ratio of the lithium iron phosphate, the ternary material, and the lithium iron manganese phosphate is: 10-60:10-50:10-50. The cathode slurry further includes a conductive agent, and the conductive agent is carbon nanotubes.

[0006] CN 106058245A discloses a low-temperature lithium-ion battery, comprising a positive electrode, a negative electrode and an electrolyte; the positive electrode active material used in the positive electrode is a ternary material of nickel-cobalt-manganese-oxide lithium doped with lithium iron manganese phosphate, wherein the doping mass percentage of lithium iron manganese phosphate in the positive electrode active material is 5% to 30%; the negative electrode active material used in the negative electrode is graphite or carbon-coated graphite material; the organic solvent used in the electrolyte is a mixed system of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate and propylene carbonate, and the concentration of lithium ions in the electrolyte is 0.9 to 1.3 mol / L.

[0007] However, in order to balance performance and safety, multiple materials are mixed, which brings up the problem of how to ensure the structural and thermal stability of the mixed positive electrode materials. Summary of the invention

[0008] In view of the problems existing in the prior art, the present invention provides a modified ternary composite lithium iron manganese phosphate material and a preparation method and application thereof. The composite ternary material and lithium iron manganese phosphate material can obtain a positive electrode material that takes into account both energy density and safety performance. Both the ternary material and the lithium iron manganese phosphate are modified by doping and coating, and the synergistic effect of doping and coating can be used to optimize the long cycle performance of the positive electrode material.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a modified ternary composite lithium manganese iron phosphate material, wherein the modified ternary composite lithium manganese iron phosphate material comprises a composite modified ternary material and a modified lithium manganese iron phosphate material;

[0011] The modified ternary material includes a ternary material, a double-layer coating layer of the ternary material and a ternary material doped with metal ions; the double-layer coating layer of the ternary material includes a ternary material metal oxide layer and a ternary material cation coating layer;

[0012] The modified lithium iron manganese phosphate material includes a lithium iron manganese phosphate material, a lithium iron manganese phosphate double-layer coating layer and lithium iron manganese phosphate doped metal ions; the lithium iron manganese phosphate double-layer coating layer includes a lithium iron manganese phosphate metal oxide layer and a lithium iron manganese phosphate cation coating layer.

[0013] The composite ternary material and lithium iron manganese phosphate material in the present invention can obtain a positive electrode material that takes into account both energy density and safety performance. The ternary material and lithium iron manganese phosphate are both modified by doping and coating, and the synergistic effect of doping and coating can be used to optimize the long cycle performance of the positive electrode material; the synergistic effect between the cationic coating layer formed in situ in the double-layer coating layer and the doped metal can inhibit the occurrence of phase change, thereby maintaining the integrity and stability of the material's microstructure, and the metal oxide layer in the double-layer coating layer is beneficial to reducing side reactions at the interface, thereby further improving the long cycle performance of the material.

[0014] Preferably, in the ternary composite lithium manganese iron phosphate, the composite mass ratio of the modified ternary material and the modified lithium manganese iron phosphate material is (0-1):1 and is not 0, for example, it can be 0.2:1, 0.4:1, 0.5:1, 0.8:1 or 0.9:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the median particle size of the modified ternary composite lithium manganese iron phosphate material is 2 to 15 μm, for example, 2 μm, 5 μm, 10 μm, 12 μm or 15 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] Preferably, the material of the ternary material metal oxide layer includes titanium dioxide.

[0017] Preferably, the material of the ternary material cation coating layer includes lithium titanate.

[0018] Preferably, the metal ions doped in the ternary material are titanium ions.

[0019] Preferably, the thickness of the double-layer coating of the ternary material is 6 to 10 nm, for example, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0020] The modified ternary material provided by the present invention has a highly stable hybrid surface structure, which includes titanium dioxide and lithium titanate coating layers and surface titanium doping of divalent titanium ions, thereby enhancing the structural stability of the material and eliminating lithium impurities on the surface of the material.

[0021] In the structure of double-layer titanium coating and doped titanium in the modified ternary material, the synergistic effect of doped titanium and in-situ formed lithium titanate cation coating inhibits the reversible phase change of the material, thereby maintaining the integrity of the material's microstructure. The electrochemically stable titanium dioxide coating can effectively protect the direct contact between the positive electrode material and the electrolyte, effectively inhibiting the occurrence of direct side reactions; the presence of the lithium titanate cation coating not only consumes the residual lithium on the surface of the material, but also promotes the transmission of lithium ions to a certain extent due to the three-dimensional lithium ion transmission channel of lithium titanate, effectively improving the capacity of the material.

[0022] In the present invention, the tightly combined titanium dioxide and lithium titanate coating layers in the double-layer coating can effectively prevent the coating layer from falling off the material surface during a long cycle, thereby maintaining the interface stability and structural stability of the material and significantly improving the cycling performance of the material.

[0023] Preferably, the material of the lithium iron manganese phosphate metal oxide layer includes titanium dioxide.

[0024] Preferably, the material of the lithium manganese iron phosphate cation coating layer includes lithium titanate.

[0025] Preferably, the metal ions doped into the lithium manganese iron phosphate are titanium ions.

[0026] Preferably, the thickness of the lithium manganese iron phosphate double-layer coating is 6-10 nm, for example, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] The modified lithium iron manganese phosphate material provided by the present invention has a highly stable hybrid surface structure, which includes titanium dioxide and lithium titanate coating layers and surface titanium doping of divalent titanium ions, thereby enhancing the structural stability of the material and eliminating lithium impurities on the surface of the material.

[0028] Surface doping with titanium induces a lithium titanate cation coating, thereby inhibiting the migration of transition metal ions, inhibiting reversible phase changes, and enhancing the structural stability of the material; the lithium titanate coating with three-dimensional channels promotes ion transport, and the electrochemically stable titanium dioxide coating inhibits side reactions and enhances interface stability. By inhibiting phase changes, the orderly arrangement of nickel ions in the lithium layer improves thermal stability.

[0029] In a second aspect, the present invention provides a method for preparing the modified ternary composite lithium manganese iron phosphate material according to the first aspect, characterized in that the preparation method comprises the following steps:

[0030] Provide modified ternary materials and modified lithium manganese iron phosphate materials;

[0031] The modified ternary material and the modified lithium manganese iron phosphate material are mixed to obtain the modified ternary composite lithium manganese iron phosphate material.

[0032] Preferably, the preparation method of the modified ternary material comprises:

[0033] The modified ternary material is obtained by mixing a ternary precursor, a lithium source and a titanium source and sintering them.

[0034] Preferably, in the ternary precursor, the molar ratio of Ni:Co:Mn is 1:1:1 to 9.5:0.25:0.25, for example, 1:1:1, 5:2:3, 7:1:2, 8:1:1 or 9.5:0.25:0.25, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] Preferably, the lithium source includes any one of lithium hydroxide, lithium carbonate, lithium nitrate or lithium acetate, or a combination of at least two of them. Typical but non-limiting combinations include a combination of lithium hydroxide and lithium carbonate, a combination of lithium carbonate and lithium nitrate, a combination of lithium nitrate and lithium acetate, a combination of lithium hydroxide, lithium carbonate and lithium nitrate, or a combination of lithium carbonate, lithium nitrate and lithium acetate.

[0036] Preferably, the titanium source comprises titanium oxide.

[0037] The preparation method of the present invention adds a small amount of titanium oxide during the preparation of the ternary material, thereby realizing overall structural modification from the surface of the material to the interior of the material, and combining titanium doping with the surface titanium dioxide and lithium titanate hybrid coating in the ternary material through a one-step mixed sintering method.

[0038] Preferably, the mass of the titanium source is 1-4wt% of the mass of the ternary precursor, for example, 1wt%, 1.5wt%, 2wt%, 3wt% or 4wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] Preferably, the sintering temperature is 750-950°C, for example, 750°C, 800°C, 850°C, 900°C or 950°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0040] Preferably, the sintering time is 10 to 15 hours;

[0041] Preferably, the sintering process further includes rolling, jaw crushing, pulverizing and demagnetizing.

[0042] Preferably, the preparation method of the modified lithium manganese iron phosphate material comprises:

[0043] The lithium iron manganese phosphate precursor, the lithium source and the titanium source are mixed, spray-dried and granulated, and calcined under a protective atmosphere to obtain the modified lithium iron manganese phosphate material.

[0044] Preferably, the titanium source comprises titanium oxide.

[0045] The preparation method of the present invention adds a small amount of titanium oxide during the preparation process of the lithium iron manganese phosphate material, thereby realizing overall structural modification from the surface of the material to the inside of the material. Through a one-step mixed sintering method, titanium doping is combined with the surface titanium dioxide and lithium titanate hybrid coating layer in the lithium iron manganese phosphate material.

[0046] Preferably, the mass of the titanium source is 1-4wt% of the mass of the lithium iron manganese phosphate precursor, for example, it can be 1wt%, 1.5wt%, 2wt%, 3wt% or 4wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] Preferably, the protective atmosphere is an inert gas atmosphere.

[0048] Preferably, the calcination temperature is 700-800°C, for example, 700°C, 720°C, 740°C, 760°C, 780°C or 800°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] Preferably, the calcination time is 8 to 10 hours, for example, 8 hours, 8.5 hours, 9 hours, 9.5 hours or 10 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0050] Preferably, the calcination further includes crushing, screening and demagnetization.

[0051] Preferably, the median particle size of the modified ternary material is 5 to 20 μm, for example, 5 μm, 8 μm, 10 μm, 15 μm or 20 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] Preferably, the median particle size of the modified lithium manganese iron phosphate material is 1 to 5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] Preferably, the mixing comprises high energy ball milling.

[0054] Preferably, the ball-to-material ratio of the high-energy ball mill is (10-20):1, for example, it can be 10:1, 12:1, 15:1, 18:1 or 20:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] Preferably, the rotation speed of the high energy ball mill is 1500-2000 rpm, for example, it can be 1500 rpm, 1600 rpm, 1700 rpm, 1800 rpm or 2000 rpm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0056] Preferably, the high energy ball milling time is 1 to 2 hours, for example, 1 hour, 1.2 hours, 1.5 hours, 1.8 hours or 2 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0057] Preferably, the mass ratio of the modified ternary material and the modified lithium manganese iron phosphate material is (0-1):1 and is not 0, for example, it can be 0.2:1, 0.4:1, 0.5:1, 0.8:1 or 0.9:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] As a preferred technical solution of the preparation method described in the second aspect of the present invention, the preparation method comprises the following steps:

[0059] A ternary precursor, a lithium source and 1-4wt% of titanium oxide by weight of the ternary precursor are mixed, sintered at 750-950° C. for 10-15 hours, and then subjected to rolling, jaw crushing, pulverizing and demagnetization to obtain the modified ternary material;

[0060] A lithium iron manganese phosphate precursor, a lithium source and titanium oxide in an amount of 1 to 4 wt% by weight of the lithium iron manganese phosphate precursor are mixed, spray dried and granulated, calcined at 700 to 800° C. for 8 to 10 hours in an inert gas atmosphere, and then crushed, sieved and demagnetized to obtain the modified lithium iron manganese phosphate material;

[0061] The modified ternary material and the modified lithium manganese iron phosphate material are mixed in a mass ratio of (0-1):1 and not 0, and high-energy ball milling is performed for 1-2 hours at a ball-to-material ratio of (10-20):1 and a rotation speed of 1500-2000 rpm to obtain the modified ternary composite lithium manganese iron phosphate material.

[0062] In a third aspect, the present invention provides a positive electrode sheet, wherein the positive electrode sheet contains the modified ternary composite lithium manganese iron phosphate material as described in the first aspect.

[0063] In a fourth aspect, the present invention provides a battery, wherein the battery contains the modified ternary composite lithium manganese iron phosphate material as described in the first aspect or the positive electrode sheet as described in the second aspect.

[0064] According to the above technical scheme, the beneficial effects of the present invention are as follows:

[0065] The composite ternary material and lithium iron manganese phosphate material in the present invention can obtain a positive electrode material that takes into account both energy density and safety performance. The ternary material and lithium iron manganese phosphate are both modified by doping and coating, and the synergistic effect of doping and coating can be used to optimize the long cycle performance of the positive electrode material; the synergistic effect between the cationic coating layer formed in situ in the double-layer coating layer and the doped metal ions can inhibit the occurrence of phase change, thereby maintaining the integrity and stability of the material's microstructure, and the metal oxide layer in the double-layer coating layer is beneficial to reducing side reactions at the interface, thereby further improving the long cycle performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1It is a scanning electron microscope image of the modified ternary material in Example 1.

[0067] Figure 2 This is a scanning electron microscope image of the modified lithium manganese iron phosphate material in Example 1.

[0068] Figure 3 This is a scanning electron microscope image of the modified ternary composite lithium manganese iron phosphate material in Example 1.

[0069] Figure 4 This is the XRD comparison diagram in Example 1. DETAILED DESCRIPTION

[0070] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0071] Example 1

[0072] This embodiment provides a modified ternary composite lithium manganese iron phosphate material, wherein the modified ternary composite lithium manganese iron phosphate material comprises a modified ternary material and a modified lithium manganese iron phosphate material in a composite mass ratio of 3:7, and the median particle size is 10 μm;

[0073] The modified ternary material (SEM) Figure 1 As shown) includes NCM523 ternary material, ternary material double-layer coating and doped titanium oxide; the thickness of the ternary material double-layer coating is 8nm, including a titanium dioxide layer and a lithium titanate cation coating layer; the median particle size of the modified ternary material is 10μm.

[0074] The modified lithium manganese iron phosphate material (Scanning electron microscope as shown in Figure 2 The modified lithium manganese iron phosphate material comprises a lithium manganese iron phosphate double-layer coating and doped titanium oxide; the thickness of the lithium manganese iron phosphate double-layer coating is 8 nm, including a titanium dioxide layer and a lithium titanate cation coating layer; the median particle size of the modified lithium manganese iron phosphate material is 2.5 μm.

[0075] The modified ternary composite lithium manganese iron phosphate material is obtained by the following preparation method:

[0076] The NCM523 ternary precursor, lithium hydroxide and 2.5wt% of titanium oxide by weight of the ternary precursor are mixed, sintered at 800° C. for 12 hours, and then subjected to rolling, jaw crushing, pulverizing and demagnetization to obtain the modified ternary material;

[0077] A lithium iron manganese phosphate precursor, lithium hydroxide and titanium oxide (2.5 wt% by weight of the lithium iron manganese phosphate precursor) are mixed, spray dried and granulated, calcined at 750° C. for 9 h in an argon gas atmosphere, and then crushed, sieved and demagnetized to obtain the modified lithium iron manganese phosphate material;

[0078] The modified ternary material and the modified lithium manganese iron phosphate material were mixed in a mass ratio of 3:7, and high-energy ball milling was performed for 1.5 h at a ball-to-material ratio of 15:1 and a rotation speed of 1800 rpm to obtain the modified ternary composite lithium manganese iron phosphate material (Scanning electron microscopy as shown in FIG. Figure 3 shown);

[0079] EDS element testing of the obtained modified ternary composite lithium manganese iron phosphate material showed that the Ti element was evenly distributed in the bulk phase of the material, indicating the presence of titanium doping.

[0080] Pure TiO2 and Ti2O3 were mixed with lithium source respectively and sintered for the same time under the experimental conditions of this embodiment. Figure 4 As shown, the XRD test shows that the XRD test results after TiO2 and lithium source are mixed and sintered correspond to pure phase TiO2; the XRD test results after Ti2O3 and lithium source are mixed and sintered correspond to the mixture of Li2TiO3 and TiO2. The results show that the double-layer coating is composed of TiO2 and Li2TiO3.

[0081] Example 2

[0082] This embodiment provides a modified ternary composite lithium manganese iron phosphate material, wherein the modified ternary composite lithium manganese iron phosphate material includes a modified ternary material and a modified lithium manganese iron phosphate material in a composite mass ratio of 1:1, and the median particle size is 2 μm;

[0083] The modified ternary material includes NCM523 ternary material, a double-layer coating of the ternary material and doped titanium oxide; the thickness of the double-layer coating of the ternary material is 6nm, including a titanium oxide layer and a lithium titanate cation coating layer; the median particle size of the modified ternary material is 5μm.

[0084] The modified lithium iron manganese phosphate material includes lithium iron manganese phosphate material, a lithium iron manganese phosphate double-layer coating layer and doped titanium oxide; the thickness of the lithium iron manganese phosphate double-layer coating layer is 6nm, including a titanium dioxide layer and a lithium titanate cation coating layer; the median particle size of the modified lithium iron manganese phosphate material is 1μm.

[0085] The modified ternary composite lithium manganese iron phosphate material is obtained by the following preparation method:

[0086] The NCM523 ternary precursor, lithium carbonate and titanium oxide (1 wt% by weight of the ternary precursor) are mixed, sintered at 750° C. for 15 h, and then subjected to rolling, jaw crushing, pulverization and demagnetization to obtain the modified ternary material;

[0087] Mixing a lithium iron manganese phosphate precursor, lithium carbonate and titanium oxide (1 wt% by weight of the lithium iron manganese phosphate precursor), spray drying and granulating, calcining at 700° C. for 10 h in an inert gas atmosphere, and then crushing, screening and demagnetizing to obtain the modified lithium iron manganese phosphate material;

[0088] The modified ternary material and the modified lithium manganese iron phosphate material are mixed in a mass ratio of 1:1, and high-energy ball milling is performed at a ball-to-material ratio of 10:1 and a rotation speed of 2000 rpm for 1 hour to obtain the modified ternary composite lithium manganese iron phosphate material.

[0089] Example 3

[0090] This embodiment provides a modified ternary composite lithium manganese iron phosphate material, wherein the modified ternary composite lithium manganese iron phosphate material includes a modified ternary material and a modified lithium manganese iron phosphate material in a composite mass ratio of 2:8, and the median particle size is 15 μm;

[0091] The modified ternary material includes NCM523 ternary material, a double-layer coating of the ternary material and doped titanium oxide; the thickness of the double-layer coating of the ternary material is 10nm, including a titanium oxide layer and a lithium titanate cation coating layer; the median particle size of the modified ternary material is 20μm.

[0092] The modified lithium iron manganese phosphate material includes lithium iron manganese phosphate material, a lithium iron manganese phosphate double-layer coating layer and doped titanium oxide; the thickness of the lithium iron manganese phosphate double-layer coating layer is 10nm, including a titanium dioxide layer and a lithium titanate cation coating layer; the median particle size of the modified lithium iron manganese phosphate material is 5μm.

[0093] The modified ternary composite lithium manganese iron phosphate material is obtained by the following preparation method:

[0094] The NCM523 ternary precursor, lithium nitrate and 4wt% of titanium oxide by weight of the ternary precursor are mixed, sintered at 950° C. for 10 hours, and then subjected to rolling, jaw crushing, pulverizing and demagnetization to obtain the modified ternary material;

[0095] A lithium iron manganese phosphate precursor, lithium nitrate and titanium oxide (4 wt% by weight of the lithium iron manganese phosphate precursor) are mixed, spray dried and granulated, calcined at 800° C. for 8 h in an inert gas atmosphere, and then crushed, sieved and demagnetized to obtain the modified lithium iron manganese phosphate material;

[0096] The modified ternary material and the modified lithium manganese iron phosphate material are mixed in a mass ratio of 2:8, and high-energy ball milling is performed for 2 hours at a ball-to-material ratio of 20:1 and a rotation speed of 1500 rpm to obtain the modified ternary composite lithium manganese iron phosphate material.

[0097] Example 4

[0098] This embodiment provides a ternary composite lithium manganese iron phosphate material, which is different from Embodiment 1 in that the composite mass ratio of the modified ternary material to the modified lithium manganese iron phosphate material is 2:1.

[0099] Example 5

[0100] This embodiment provides a ternary composite lithium manganese iron phosphate material, which differs from Embodiment 1 in that titanium oxide is replaced by an equal mass of titanium dioxide in the preparation method of the modified ternary material.

[0101] Example 6

[0102] This embodiment provides a ternary composite lithium manganese iron phosphate material, which is different from Embodiment 1 in that the amount of titanium oxide added in the preparation method of the modified ternary material is 0.5 wt %.

[0103] Example 7

[0104] This embodiment provides a ternary composite lithium manganese iron phosphate material, which is different from Embodiment 1 in that the amount of titanium oxide added in the preparation method of the modified ternary material is 4.5 wt %.

[0105] Example 8

[0106] This embodiment provides a ternary composite lithium manganese iron phosphate material, which differs from Embodiment 1 in that titanium oxide is replaced by titanium dioxide of equal mass in the preparation method of the modified lithium manganese iron phosphate material.

[0107] Example 9

[0108] This embodiment provides a ternary composite lithium manganese iron phosphate material, which is different from Embodiment 1 in that the amount of titanium oxide added in the preparation method of the modified lithium manganese iron phosphate material is 0.5 wt %.

[0109] Example 10

[0110] This embodiment provides a ternary composite lithium manganese iron phosphate material, which is different from Embodiment 1 in that the amount of titanium oxide added in the preparation method of the modified lithium manganese iron phosphate material is 4.5 wt %.

[0111] Embodiment 11

[0112] This embodiment provides a ternary composite lithium manganese iron phosphate material, which is different from Embodiment 1 in that the preparation method of the ternary composite lithium manganese iron phosphate material includes the following steps:

[0113] The ternary precursor and the lithium source are mixed, sintered at 800° C. for 12 hours, and then subjected to rolling, jaw crushing, pulverizing and demagnetization to obtain the ternary material;

[0114] The lithium iron manganese phosphate precursor and the lithium source are mixed, spray-dried and granulated, calcined at 750° C. for 9 hours under an inert gas atmosphere, and then crushed, sieved and demagnetized to obtain the lithium iron manganese phosphate material;

[0115] 2.5 wt % of titanium oxide and the ternary material and lithium manganese iron phosphate material in a mass ratio of 3:7 are mixed and subjected to high-energy ball milling to obtain the modified ternary composite lithium manganese iron phosphate material.

[0116] Comparative Example 1

[0117] This comparative example provides a ternary composite lithium manganese iron phosphate material, which differs from Example 1 in that titanium oxide is not added in the entire preparation method.

[0118] The above-obtained ternary composite lithium manganese iron phosphate material was used to prepare positive electrode slurry according to the positive electrode material: SP: CNT: PVDF = 97: 0.4: 0.5: 2.1, and coated on a 12μm carbon-coated aluminum foil to obtain a positive electrode sheet; the negative electrode slurry was prepared according to graphite: SP: CMC: SBR = 97: 0.7: 1.25: 1.05, and coated on an 8μm copper foil to obtain a negative electrode sheet. The diaphragm used was 9+2+1μm. The electrolyte was EC: DEC: EMC = 4: 3: 3, the mass of additives accounted for 10% of the total mass, of which VC: PS: FEC: CHB = 3: 2: 1: 1, and the concentration of lithium hexafluorophosphate in the electrolyte was 1mol / L. The corresponding positive and negative electrode sheets and separators are wound or stacked to obtain bare cells, which are then placed in an outer packaging aluminum-plastic film to be assembled into 2Ah soft-pack cells, into which electrolyte is injected, and after aging, formation, shaping, packaging and other processes, a soft-pack lithium-ion battery is obtained for testing.

[0119] The results are shown in Table 1.

[0120] Table 1

[0121]

[0122]

[0123] The following conclusions can be drawn from Table 1:

[0124] (1) It can be seen from Examples 1-3 and Comparative Example 1 that the composite ternary material and lithium manganese iron phosphate material can obtain a positive electrode material that takes into account both energy density and long cycle performance. The ternary material and lithium manganese iron phosphate are both modified by doping and coating, and the synergistic effect of doping and coating can be used to optimize the long cycle performance of the positive electrode material; the gram capacity of the ternary composite lithium manganese iron phosphate material provided by the present invention is ≥158mAh / g, the soft package energy density is ≥200Wh / kg, and the 1C cycle 200 week retention rate is ≥97.1%.

[0125] (2) From the comparison between Example 4 and Example 1, it can be seen that when the composite mass ratio of the modified ternary material and the modified lithium manganese iron phosphate material is not within the preferred range provided by the present invention, the composite ternary material and the lithium manganese iron phosphate material are not conducive to obtaining a positive electrode material that takes into account both energy density and long cycle performance.

[0126] (3) From the comparison between Examples 5-10 and Example 1, it can be seen that when titanium oxide is replaced by other titanium sources, or the amount of titanium oxide added is not within the preferred range of the present invention, it is impossible to achieve simultaneous modification of titanium doping and surface double-layer coating through a one-step mixed sintering method, thereby affecting the structure of the material from the surface to the inside, which is not conducive to the improvement of its cycle performance and energy density.

[0127] (4) From the comparison between Example 11 and Example 1, it can be seen that when compounding is performed first and then coating is performed, the coating layer is uneven due to the close contact between the ternary material and the lithium manganese iron phosphate material, and the electrical properties of the material cannot be improved well.

[0128] In summary, the composite ternary material and lithium manganese iron phosphate material in the present invention can obtain a positive electrode material that takes into account both energy density and safety performance. Both the ternary material and the lithium manganese iron phosphate are modified by doping and coating, and the synergistic effect of doping and coating can be used to optimize the long cycle performance of the positive electrode material.

[0129] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A modified ternary composite lithium manganese iron phosphate material, It is characterized in that The modified ternary composite lithium manganese iron phosphate material includes a composite modified ternary material and a modified lithium manganese iron phosphate material; The modified ternary material includes a ternary material, a double-layer coating layer of the ternary material and a ternary material doped with metal ions; the double-layer coating layer of the ternary material includes a ternary material metal oxide layer and a ternary material cation coating layer; The material of the ternary material metal oxide layer includes titanium dioxide, the material of the ternary material cationic coating layer includes lithium titanate, and the metal ions doped in the ternary material are divalent titanium ions; The modified lithium iron manganese phosphate material includes a lithium iron manganese phosphate material, a lithium iron manganese phosphate double-layer coating layer and lithium iron manganese phosphate doped metal ions; the lithium iron manganese phosphate double-layer coating layer includes a lithium iron manganese phosphate metal oxide layer and a lithium iron manganese phosphate cation coating layer; The material of the lithium manganese iron phosphate metal oxide layer includes titanium dioxide; the material of the lithium manganese iron phosphate cation coating layer includes lithium titanate; the lithium manganese iron phosphate doped metal ions are titanium ions; The modified ternary composite lithium manganese iron phosphate material is prepared by the following method, which comprises the following steps: Provide modified ternary materials and modified lithium manganese iron phosphate materials; The preparation method of the modified ternary material comprises: Mixing a ternary precursor, a lithium source and a titanium source, and sintering to obtain the modified ternary material; The preparation method of the modified lithium manganese iron phosphate material comprises: Mixing a lithium iron manganese phosphate precursor, a lithium source and a titanium source, spray drying and granulating, and calcining under a protective atmosphere to obtain the modified lithium iron manganese phosphate material; The modified ternary material and the modified lithium manganese iron phosphate material are mixed to obtain the modified ternary composite lithium manganese iron phosphate material.

2. The modified ternary composite lithium manganese iron phosphate material according to claim 1, It is characterized in that In the modified ternary composite lithium manganese iron phosphate material, the composite mass ratio of the modified ternary material to the modified lithium manganese iron phosphate material is (0~1):1, and is not 0.

3. The modified ternary composite lithium manganese iron phosphate material according to claim 1, It is characterized in that The median particle size of the modified ternary composite lithium manganese iron phosphate material is 2-15 μm.

4. The modified ternary composite lithium manganese iron phosphate material according to claim 1, It is characterized in that The thickness of the double-layer coating of the ternary material is 6-10 nm.

5. The modified ternary composite lithium manganese iron phosphate material according to claim 1, It is characterized in that The thickness of the lithium manganese iron phosphate double-layer coating is 6-10 nm.

6. A method for preparing the modified ternary composite lithium manganese iron phosphate material according to any one of claims 1 to 5, It is characterized in that The preparation method comprises the following steps: Provide modified ternary materials and modified lithium manganese iron phosphate materials; The preparation method of the modified ternary material comprises: Mixing a ternary precursor, a lithium source and a titanium source, and sintering to obtain the modified ternary material; The preparation method of the modified lithium manganese iron phosphate material comprises: Mixing a lithium iron manganese phosphate precursor, a lithium source and a titanium source, spray drying and granulating, and calcining under a protective atmosphere to obtain the modified lithium iron manganese phosphate material; The modified ternary material and the modified lithium manganese iron phosphate material are mixed to obtain the modified ternary composite lithium manganese iron phosphate material.

7. The preparation method according to claim 6, It is characterized in that In the ternary precursor, the molar ratio of Ni:Co:Mn is 1:1:1~9.5:0.25:0.

25.

8. The preparation method according to claim 6, It is characterized in that In the preparation method of the modified ternary material, the lithium source includes any one of lithium hydroxide, lithium carbonate, lithium nitrate or lithium acetate, or a combination of at least two of them.

9. The preparation method according to claim 6, It is characterized in that In the method for preparing the modified ternary material, the titanium source includes titanium oxide.

10. The preparation method according to claim 6, It is characterized in that In the preparation method of the modified ternary material, the mass of the titanium source is 1-4wt% of the mass of the ternary precursor.

11. The preparation method according to claim 6, It is characterized in that In the preparation method of the modified ternary material, the sintering temperature is 750-950°C.

12. The preparation method according to claim 6, It is characterized in that In the preparation method of the modified ternary material, the sintering time is 10 to 15 hours.

13. The preparation method according to claim 6, It is characterized in that In the preparation method of the modified ternary material, the sintering further includes rolling, jaw crushing, pulverizing and demagnetizing.

14. The preparation method according to claim 6, It is characterized in that In the preparation method of the modified lithium manganese iron phosphate material, the titanium source includes titanium oxide.

15. The preparation method according to claim 6, It is characterized in that In the preparation method of the modified lithium manganese iron phosphate material, the mass of the titanium source is 1-4wt% of the mass of the lithium manganese iron phosphate precursor.

16. The preparation method according to claim 6, It is characterized in that In the preparation method of the modified lithium manganese iron phosphate material, the protective atmosphere is an inert gas atmosphere.

17. The preparation method according to claim 6, It is characterized in that In the preparation method of the modified lithium manganese iron phosphate material, the calcination temperature is 700-800°C.

18. The preparation method according to claim 6, It is characterized in that In the preparation method of the modified lithium manganese iron phosphate material, the calcination time is 8 to 10 hours.

19. The preparation method according to claim 6, It is characterized in that In the preparation method of the modified lithium manganese iron phosphate material, the calcination further includes crushing, screening and demagnetization.

20. The preparation method according to claim 6, It is characterized in that The median particle size of the modified ternary material is 5-20 μm.

21. The preparation method according to claim 6, It is characterized in that The median particle size of the modified lithium manganese iron phosphate material is 1-5 μm.

22. The preparation method according to claim 6, It is characterized in that The mixing includes high energy ball milling.

23. The preparation method according to claim 22, It is characterized in that The ball-to-material ratio of the high-energy ball mill is (10-20):

1.

24. The preparation method according to claim 22, It is characterized in that The rotation speed of the high energy ball mill is 1500-2000 rpm.

25. The preparation method according to claim 22, It is characterized in that The high energy ball milling time is 1 to 2 hours.

26. The preparation method according to claim 6, It is characterized in that The mass ratio of the modified ternary material to the modified lithium iron manganese phosphate material is (0~1):1, and is not 0.

27. The preparation method according to claim 6, It is characterized in that The preparation method comprises the following steps: A ternary precursor, a lithium source and 1-4wt% of titanium oxide by weight of the ternary precursor are mixed, sintered at 750-950° C. for 10-15 hours, and then subjected to rolling, jaw crushing, pulverizing and demagnetization to obtain the modified ternary material; A lithium iron manganese phosphate precursor, a lithium source and titanium oxide in an amount of 1 to 4 wt% by weight of the lithium iron manganese phosphate precursor are mixed, spray dried and granulated, calcined at 700 to 800° C. for 8 to 10 hours under an inert gas atmosphere, and then crushed, sieved and demagnetized to obtain the modified lithium iron manganese phosphate material; The modified ternary material and the modified lithium manganese iron phosphate material are mixed in a mass ratio of (0-1):1 and not 0, and high-energy ball milling is performed for 1-2 hours at a ball-to-material ratio of (10-20):1 and a rotation speed of 1500-2000 rpm to obtain the modified ternary composite lithium manganese iron phosphate material.

28. A positive electrode sheet, It is characterized in that The positive electrode sheet contains the modified ternary composite lithium manganese iron phosphate material as described in any one of claims 1 to 5.

29. A battery, It is characterized in that The battery contains the modified ternary composite lithium manganese iron phosphate material as described in any one of claims 1 to 5 or the positive electrode sheet as described in claim 28.

Citation Information

Patent Citations

  • Mixed positive electrode material, positive plate using the same, and lithium ion battery

    CN104300123A

  • Lithium ion battery

    CN105449269A

  • Low temperature lithium ion battery

    CN106058245A

  • Lithium iron phosphate positive electrode material modified surface structure, and preparation method and application thereof

    CN108878873A

  • Preparation method of lithium-containing compound-coated and ion-doped ternary positive electrode material

    CN112614974A